Enantioselective Synthesis of Planar Chiral Ferrocifens that Show Chiral Discrimination in Antiproliferative Activity on Breast Cancer Cells. (30th June 2020) - Cunningham, Laura; Wang, Yong; Nottingham, Chris; Pagsulingan, Jammah; Jaouen, Gérard; McGlinchey, Michael J.; Guiry, Patrick J.
Abstract: The design and first enantioselective synthesis of a series of chiral ferrocifens and ferrociphenols was realised by enantioselective palladium‐catalysed intramolecular direct C−H bond activation followed by McMurry coupling. Biological evaluation revealed moderate anticancer activities on breast cancer cells and evidence of chiral discrimination between enantiomers. Treatment of the novel ferrocifens with Ag2 O revealed that these systems are unable to form a neutral quinone methide, yet still demonstrate marked antiproliferative properties against both the hormone‐dependent MCF‐7 and hormone‐independent MDA‐MB‐231 cell lines. This bioactivity arises from two mechanisms: Fenton‐type chemistry and the anti‐estrogenic activity associated with the tamoxifen‐like structure. Abstract : Inaccessible no longer : Enantiopure ferrocifens and ferrociphenols have been efficiently prepared for biological evaluation via a chiral ketone by palladium‐catalysed intramolecular direct C−H bond activation/cyclisation. IC50 values reveal that S ‐configured molecules perform better against an ER+ breast cancer cell line, but the result is less clear in the ER− case.